2007
DOI: 10.1080/17453670710014455
|View full text |Cite
|
Sign up to set email alerts
|

Hamstring tendon autograft better than bone–patellar tendon–bone autograft in ACL reconstruction—a cumulative meta-analysis and clinically relevant sensitivity analysis applied to a previously published analysis

Abstract: Hamstring tendon autograft better than bone-patellar tendon-bone autograft in ACL reconstruction-a cumulative meta-analysis and clinically relevant sensitivity analysis applied to a previously published analysis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…The same results were demonstrated in the meta-analysis by Poolman et al and Biauet al, who found Lachman to be in favor of the BPTB group in their overall analyses, but when restricted to the four-strand HT autograft with femoral fixation of endobutton, the two autografts seemed to be equal regarding this outcome [10,12]. Mohtadi et al while they reported significantly lower rates for positive Lachman for the BPTB group compared to the HT group, they did not find the same results in any of the subgroup analysis they conducted, except the subgroup analysis of quasi-RCTs, and this is strong evidence of the impact non-RCTs have on the general results [15].…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…The same results were demonstrated in the meta-analysis by Poolman et al and Biauet al, who found Lachman to be in favor of the BPTB group in their overall analyses, but when restricted to the four-strand HT autograft with femoral fixation of endobutton, the two autografts seemed to be equal regarding this outcome [10,12]. Mohtadi et al while they reported significantly lower rates for positive Lachman for the BPTB group compared to the HT group, they did not find the same results in any of the subgroup analysis they conducted, except the subgroup analysis of quasi-RCTs, and this is strong evidence of the impact non-RCTs have on the general results [15].…”
Section: Discussionsupporting
confidence: 67%
“…The remaining five reported a total number of patients [15][16]20,[23][24], one reported the total sample and specified the graft the majority received, but a small number remained unknown [19]. Another one reported a number of series [9] and three did not specify the sample size [12,14,17]. Twenty-one of the studies reported on short-term outcomes [5][6][7][8][9][10][11][12][13][15][16][17][18][19][21][22][23][24][25]27,30], four on long-term outcomes [14,20,[28][29], and another reported one on all three, short-, mid-, and long-term outcomes [26].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Casteleyn states that the real benchmark of success in the treatment of ACL ruptures has to be the avoidance of treatment morbidity, secondary surgery, and osteoarthritis [ 11 ]. In the meta-analysis of Biau et al [ 7 ], 13–22 % of the patients complained of persisting knee pain, mainly associated with donor-site morbidity. The DIS technique requires no additional ligament extraction, thus minimizing the surgical trauma.…”
Section: Discussionmentioning
confidence: 99%